Pengaruh Bauran Pemasaran Terhadap Loyalitas Pelanggan Zoya Cabang Medan Dengan Brand Image Sebagai Variabel Moderating - Lisa Anggi Nauli Siregar; Isnaini Harahap (Universitas Islam Negeri Sumatera Utara, 2019)
Customer loyalty is customer loyalty to companies, brands and products, where this loyalty is influenced by various factors such as marketing mix, product, price, location and promotion and influenced by brand image as a moderating variable. This study aims to explain the effect of product, price, location and promotion on Zoya customer loyalty with brand image as a moderating variable. This research is quantitative research and the method to determine the sample is the Lemeshow formula with a sample size of 100 respondents. Data is obtained by distributing questionnaires that have been structured to the respondents. The data analysis technique used is the MRA (Moderating Regression Analysis). The results showed that as partially the product had a positive and significant effect on customer loyalty by 22.3%, the price had a positive and significant effect on customer loyalty by 35.7%, the location did not affect customer loyalty and promotion had a positive effect and significant to customer loyalty of 21.1%. The prices, locations and promotions simultaneously have a positive and significant effect on customer loyalty. And products, prices, locations and promotions have a positive effect on customer loyalty by moderating the brand image in Zoya Medan Branch.